BUILDING BRIDGES TO HEALTH: SOCIAL WORK INTERVENTIONS FOR OVERCOMING ACCESS CHALLENGES IN TRIBAL HEALTHCARE IN RAIGAD, MAHARASHTRA - Patekar, Shwetambari Chetan; Ranawat, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Among the biggest problems indigenous peoples in rural India still suffer is not being able to visit a good hospital. The aim of this project is to look into the challenges faced by tribal people in the main Raigad area of Maharashtra in trying to obtain medical care and the possible advantages of social work therapy. Within the parameters of this study, social workers and nearby medical specialists use analytical and quantitative reasoning to assess the success of community-funded programs. The study looks into how involved communities are, how much healthcare is used, and how successful the intervention is both before and after it is put into place. More proof is provided by the results of the need of putting into practice environmentally friendly and community-driven policies to improve healthcare access. This paper adds to the expanding corpus of work on the subject of using social service strategies to enhance the use of medical supervision among underprivileged people.